(untitled) (Research, Society and Development, 2021)
The evolution of the brazilian agricultural market has changed the process of production, export and consumption of food commodities. In view of that, new studies on the relationship between the food market and other markets were developed, seeking to explain the link between the prices of agricultural and non-agricultural commodities. In order to contribute to this study, the intrinsic long-term correlations between the prices of brazilian food markets were investigated, using Econophysics techniques. The daily series of prices and price return of chicken meat, soybeans and corn, recorded between 02/02/2004 and 06/16/2017 by the Centro de Estudos Avançados em Economia Aplicada / Escola Superior de Agricultura Luiz de Queiroz / Universidade de São Paulo - CEPEA/ESALQ/USP, were, therefore, investigated. The correlations between the time series were analysed using the methods Detrended Fluctuation Analysis (DFA) and Detrended Cross Correlation Analysis (DCCA), to calculate the Detrended Cross Correlation Coefficient (DCCA Coefficient), which serve to quantify long term cross correlations between non-stationary time series. The results point to the absence of cross correlations for temporal scales up to 30 days and, for larger scales, indicate correlations between chicken and corn prices stronger than between chicken and soy prices. After the 2008 food crisis, however, the correlations between the daily series of chicken meat and corn price return decreased, while in the case of chicken and soy, the correlations increased on the small scales and decreased on the larger ones.